Behavioral Diversity Across Classic Rodent Models Is Sex-Dependent - Colom-Lapetina, José; Li, Anna J.; Pelegrina-Perez, Tatiana C.; Shansky, Rebecca M. (Frontiers in Behavioral Neuroscience, 2019)
Symptoms of trauma and stressor related disorders such as PTSD often develop well after the traumatic experience has occurred, and so identifying early predictors of risk or resilience is important for the implementation of interventional therapies. For example, passive coping strategies such as tonic immobility and peritraumatic dissociation during the trauma itself are risk factors for the developments of PTSD, especially in women. However, discrete, sex-specific coping responses that predict later outcomes in animal models have not been rigorously defined. Recently, we identified an active, escape-like response exhibited primarily by a subset of female rats in a classic auditory fear conditioning task (“darting”). Here, we asked whether darting during conditioning predicted active responding in a single forced swim session (SFS) to study the potential for darting to reflect a trait-like behavioral strategy that translated across stress models. Male and female Sprague Dawley rats were tested in auditory fear conditioning acquisition and memory tests to identify Darters, and then a 15-minute forced swim session two weeks later. We observed a significant effect of sex in conditioned freezing behavior, with males exhibiting greater freezing than females across conditioning and testing trials in comparison to females. However, females demonstrated higher velocities in response to shock presentations, and were more likely to exhibit darting behavior in response to the conditioned stimulus. In SFS measures, females engaged in active behaviors such as climbing, head shaking, and diving in greater proportions than males, while males spent more time immobile throughout testing. Despite females exhibiting a more diverse behavioral repertoire in both tests, Darters did not differ from Non-darters in any SFS measure. These results suggest that the propensity to dart does not reflect a simple hyperactivity, and that despite conceptual overlap across the two tests (inescapable stress exposure and the ability to measure active vs. passive coping), the behavioral strategies engaged by an individual animal in each are likely driven by discrete mechanisms. We discuss potential challenges in interpretation of standard behavioral outcomes in classic models across the sexes, and consider the potential need for novel models that better tap into motivational states in females.